Alignment of CSR Strategies with Business Objectives in IT Sector, Focusing on the Competitive Advantage - Saeidi , Sayedeh parastoo; Saeidi , Sayyedeh Parisa; Saeidi , Parvaneh (International Journal of Membrane Science and Technology, 2023)
While numerous researchers have focused on examining the impact of Corporate Social Responsibility (CSR) on various aspects of business in different industries, there still remains a research gap in conducting comprehensive analyses of CSR strategies in Information Technology (IT) sector. Therefore, this study aims to address this gap by evaluating the effects of CSR on competitive advantage in the IT companies. In order to analyze data, AMOS structural equation modeling (AMOS-SEM) method was applied, and data were collected during February-April 2023 from 143 Iranian IT firms where CSR has not been appropriately dealt within theoretical as well as practical terms. The findings reveal that among the four components of CSR — legal, ethical, economic, and discretionary—, ethical, legal, economic, and discretionary dimensions have the most positive impact on competitive advantage, respectively. Taken together, these findings suggest a significant role for CSR in enhancing the level of competitive advantage in IT companies. In addition to the knowledge contribution, this study holds significant practical implications for IT company managers to strengthen their decision-making processes and develop effective CSR strategies.